2016
DOI: 10.3892/etm.2016.3730
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of higenamine ameliorates collagen-induced arthritis through heme oxygenase-1 and PI3K/Akt/Nrf-2 signaling pathways

Abstract: Abstract. Existing in Ranunculaceae Aconitum and tomato, with the chemical name 1-phydroxybenzyl-1,2,3,4-tetrahydroisoquinoline, higenamine is widely distributed in China. Higenamine's anti-inflammatory, antioxidant and anti-apoptotic effects have been identified in previous studies. The present study attempted to determine the protective effect of higenamine against collagen-induced arthritis through heme oxygenase-1 (HO-1) and PI3K/Akt/Nrf-2 signaling pathways. A type II collagen (CII)-induced arthritis (CIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Higenamine (synonym norcoclaurine) is a tetrahydroisoquinoline found in several plants, including aconite root [ 1 ], lotus ( Nelumbo nucifera ) [ 2 ], Gnetum parvifolium [ 3 ], Tinospora crispa [ 4 ], and Tinospora cordifolia [ 5 ]. It possesses β-adrenergic receptor agonist activity owing to its structural similarity to catecholamine, has been shown to have a tracheal relaxation effect on guinea pig trachea [ 6 ]; it can protect against myocyte apoptosis in ischemia/reperfusion injury [ 7 ], collagen-induced arthritis, and spinal cord injury [ 8 , 9 ]; and it is clinically studied for therapeutic effects [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Higenamine (synonym norcoclaurine) is a tetrahydroisoquinoline found in several plants, including aconite root [ 1 ], lotus ( Nelumbo nucifera ) [ 2 ], Gnetum parvifolium [ 3 ], Tinospora crispa [ 4 ], and Tinospora cordifolia [ 5 ]. It possesses β-adrenergic receptor agonist activity owing to its structural similarity to catecholamine, has been shown to have a tracheal relaxation effect on guinea pig trachea [ 6 ]; it can protect against myocyte apoptosis in ischemia/reperfusion injury [ 7 ], collagen-induced arthritis, and spinal cord injury [ 8 , 9 ]; and it is clinically studied for therapeutic effects [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Induction of ROS and MDA production, and SOD activity inhibition arising from neuronal cell injury triggered by oxygen-glucose deprivation/reperfusion were attenuated by Hig [46] . Hig increased antioxidant level and reduced MDA, TNF-α and IL-1β levels in a collagen-induced arthritis study [47] . According to published reports, Hig possesses a variety of pharmacological properties, including dilatation of blood vessels and bronchi, immunomodulatory, antiinflammatory, antiapoptocic and antioxidation features [18] .…”
Section: Discussionmentioning
confidence: 90%
“…These findings suggested that the NRF-2/HO-1/HMGB1 signalling pathway is involved in the anti-apoptotic activity of HG, which is consistent with the findings of Ha et al (2012), indicating that HG promotes HO-1 secretion and inhibits HMGB1 expression via the PI3K/ AKT/NRF-2 signalling pathway to improve cerebral ischaemia-reperfusion injury. HG not only inhibits apoptosis in ischaemia-reperfusion injury but also alleviates collageninduced arthritis by promoting HO-1 release and regulating the PI3K/AKT/NRF-2 signalling pathway (Duan et al, 2016). The proliferation, differentiation and apoptosis of normal cells are tightly regulated by the PI3K/AKT signalling pathway.…”
Section: Anti-apoptotic Activity Of Higenaminementioning
confidence: 99%